Shakespeare's sonnets - Shakespeare, William, 1564-1616 (Arden Shakespeare, 2010)
Shakespeare's Sonnets are universally loved and much-quoted throughout the world. First published in 1997 to much critical acclaim, the Sonnets has been a consistent best-seller in the Arden Shakespeare series. Katherine Duncan-Jones tackles the controversies and mysteries surrounding these beautiful poems head on, and explores the issues of sexuality to be found in them, making this a truly modern edition for today's readers and students. This revised edition has been updated and corrected in the light of new scholarship and critical thinking since its first publication.